Momentum dependence of in-medium potentials: A solution to the hyperon puzzle in neutron stars - Chorozidou, Arsenia; Gaitanos, Theodoros (HNPS Advances in Nuclear Physics, 2025)
Neutron stars offer a great opportunity to study highly compressed hadronic matter experimentally and theoretically. However, the so-called hyperon-puzzle arises at neutron star densities. The hyperon coexistence with other particles in compressed matter softens the equation of state and many widely accepted models fail to reproduce precise observations of large neutron star masses. Here, we propose a mechanism to retain the stiffness of the high-density state with hyperons by considering the explicit momentum dependence of their in-medium potentials. Our approach modifies conventional strangeness threshold conditions and generates threshold effects on hyperons in high-density matter. We demonstrate these effects within the nonlinear derivative model, which incorporates baryon momentum-dependent fields based on empirical and microscopic studies. It turns out that even soft momentum-dependent strangeness fields do prohibit their populations in neutron star matter. The generic momentum dependence of strangeness potentials, as modeled by the nonlinear derivative approach, is crucial for resolving the long-standing hyperon-puzzle in neutron stars.